Optimalisasi konduktivitas ionik dan sifat mekanik bahan polimer elektrolit padat baterai berbasis kitosan dengan penambahan plasticizer (etilen glikol dan gliserol) (Optimization of ionic conductivity and mechanical properties of chitosan-based solid electrolyte polymer materials with the addition of plasticizers (ethylene glycol and glycerol) - Luzi Lovita NK; - Syakbaniah; Evi Yulianti (PILLAR OF PHYSICS, 2015)
Have been obtained solid-state electrolyte based on chitosan by the casting technique from a solution containing  of chitosan, montmorillonite, LiClO4 and plasticizer by using two different types of plasticizers are: ethylene glycol and glycerol. This study  purpose to know what is the concentration of ethylene glycol and glycerol as plasticizer can be obtained solid-state electrolyte based on chitosan with ionic conductivity and mechanical properties are optimum for rechargeable battery applications.  Ionic conductivity properties were characterized by  using LCR meter, mechanical properties were characterized by  mechanical tests, and microstructure using optical microscopy. The results showed that the optimum composition obtained in 50% ethylene glycol with an ionic conductivity of 1,26 x 10-3 S/cm, tensile strength of 41,59 MPa and 77,5% elongation. At the optimum conditions obtained in glycerol concentration of 25% with an ionic conductivity of 2,51 x 10-3 S / cm, tensile strength of 32,14 MPa and 69,3% elongation. Of both plasticizer, glycerol give better ionic conductivity and films produced by using glycerol are smoother and it`s texture looks more evenly, while ethylene glycol gives better mechanical properties.